Law Enforcement of Police Discretion to Resolve Traffic Accidents at the Investigation Level - Angga Nurhadinata; Candra Wibowo; Harmono Harmono; Agus Dimyati (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Traffic accidents are one of the serious problems that are often faced in the context of law enforcement, especially in countries with high traffic density such as Indonesia. This study aims to evaluate how discretionary decisions taken by police investigators can affect the case settlement process, taking into account aspects of justice and public interest. The study utilized policy documents as the primary data source, focusing on analyzing these documents through a systematic document analysis and content analysis approach. The document analysis technique will help in organizing and summarizing these documents to identify relevant information and protocols regarding the application of discretion. The content analysis will then be employed to examine the specifics of how discretion is framed and regulated within these policies, revealing the underlying principles and standards guiding police decision-making in traffic accident cases. This research would contribute to refining policies and practices related to police discretion, ensuring they effectively balance flexibility with adherence to legal and ethical standards.